The art of disarming: body, writing and performative devices in dark times (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Devices for developing exercises of attention, writing and performative practices are presented here as means of investigating habits of perception, stimulating the invention of languages and forms of sharing, and engaging with artistic and educational spaces, within the perspective of an expanded scene. Alongside the presentation of the procedures themselves, reflections are developed in relation to the context of crises within which artistic and educational activities are inserted today, particularly in Brazil. The propositions presented dialogue with traditional, artistic and academic knowledge, connecting sensorial, perceptual, emotional and cognitive dimensions in order to construct collective spaces and experiences. The paper integrates, in its very form, the procedures of the research, interweaving theoretical reflections with short accounts and images that converse indirectly with the themes approached.
Keywords: Perception; Body; Writing; Performance; Crisis